Assessing antibiotic utilization among pediatric patients in Gaborone, Botswana. (June 2022) - Kitt, Eimear; Hayes, Molly; Ballester, Lance; Sewawa, Kgotlaetsile B; Mulale, Unami; Mazhani, Loeto; Arscott-Mills, Tonya; Coffin, Susan E; Steenhoff, Andrew P
Objectives: Over the past decade, concerning trends in antimicrobial resistance have emerged in Southern Africa. Given a paucity of pediatric data, our objectives were to (1) describe antibiotic utilization trends at a national referral center in Southern Africa and (2) assess the proportion of patients receiving antibiotics appropriately. In addition, risk factors for inappropriate use were explored. Methods: We performed a prospective cohort study on medical and surgical pediatric patients aged below 13 years admitted to the country's tertiary care referral hospital in Gaborone, Botswana. We collected demographics, clinical, laboratory, and microbiology details, in addition to information on antibiotic use. We separately categorized antibiotic prescriptions using the World Health Organization AWaRe Classification of Access, Watch, and Restrict. Results: Our final cohort of 299 patients was 44% female and 27% HIV-exposed; most (68%) were admitted to the General Pediatrics ward. Infections were a common cause of hospitalization in 29% of the cohort. Almost half of our cohort were prescribed at least one antibiotic during their stay, including 40% on admission; almost half (47%) of these prescriptions were deemed appropriate. At the time of discharge, 52 (21%) patients were prescribed an antibiotic, of which 37% were appropriate. Of all antibiotics prescribed, 42% were from the World Health Organization Access antibiotic list, 58% were from the Watch antibiotic list, and 0% were prescribed antibiotics from the Restrict antibiotic list. Univariate analyses revealed that surgical patients were significantly more likely to have inappropriate antibiotics prescribed on admission. Patients who were treated for diseases for which there was a clinical pathway, or who had blood cultures sent at the time of admission were less likely to have inappropriate antibiotics prescribed. On multivariate analysis, apart from admission to the surgical unit, there were no independent predictors for inappropriate antibiotic use, although there was a trend for critically ill patients to receive inappropriate antibiotics. Conclusion: Our study reveals high rates of antibiotic consumption, much of which was inappropriate. Promising areas for antimicrobial stewardship interventions include (1) standardization of management approaches in the pediatric surgical population and (2) the implementation of feasible and generalizable clinical pathways in this tertiary care facility.